Possessor of Two Waist Belts Asmā’ bint Abu Bakr Al-Siddiq (May Allah Bless Them) A study in her Biography - moiad, nidal (lark, 2021)
In our view of Islamic heritage and throughout our long history it will be found that it always providing us with immortal women in history, surrounded by ideas, which must be resurrected, examined, studied, and employed to serve humanity. Because women were no less believing in God, sacrifice, fortitude, patience, and Jihad to uphold the word of God almighty than men, the Sahaba’a is the name of Abu Bakr’s daughter (May God bless them) as an example to follow, and a beacon follows in the era of the message until the end of the Umayyad era, so the tagged research for the names of Abu Bakr’s daughter, who belongs to the son of Tim al-Quraishiya, who was at the beginning of the call with her father Abu Bakr al-Siddiq (God bless them), and her surname is the Messenger of God (god willing) in the same two ranges because she broke her scope in half while transporting food to the Messenger of God and her father Abu Bakr to Gar Thor when they migrated to the city. She lived on the time of Messenger of God (PBUH) and she has related kinship with him due to marrying her sister the mother of believers Aisha (May God bless her), so she had preserved many Hadiths from him, and a large number from companions and followers heard from her, which indicates that is narrator, died a year (73 Ah /692 AD) and she reached a hundred years, and her lost her. She lived on the time of Messenger of God (PBUH) and she has related kinship with him due to marrying her sister the mother of believers Aisha (May God bless her), so she had preserve many Hadiths from him, and a large number from companions and followers heard from her, which indicates that he is narrator, she died a year (73 Ah /692 AD) and she reached a hundred years, and her lost her vision..